2017
DOI: 10.1016/j.ecolecon.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception of Climate Change: Empirical Evidence for Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 44 publications
(30 reference statements)
4
35
0
5
Order By: Relevance
“…One major contribution of the PMT is its illustration of the linkage between hazard perception and risk reduction behaviors. For example, Frondel et al [26] and Ling et al [27] both confirmed that flood experience was positively correlated with adaptation efforts, while Lawrence et al [28] maintained that the witnessing of major floods among German residents failed to encourage people to take more active mitigation actions. Therefore, attitude or perception may not be a good behavior predictor [29].…”
Section: The Linkages Between Risk Experience Perception and Mitigamentioning
confidence: 80%
See 1 more Smart Citation
“…One major contribution of the PMT is its illustration of the linkage between hazard perception and risk reduction behaviors. For example, Frondel et al [26] and Ling et al [27] both confirmed that flood experience was positively correlated with adaptation efforts, while Lawrence et al [28] maintained that the witnessing of major floods among German residents failed to encourage people to take more active mitigation actions. Therefore, attitude or perception may not be a good behavior predictor [29].…”
Section: The Linkages Between Risk Experience Perception and Mitigamentioning
confidence: 80%
“…While we hypothesized such a linkage, the direction of effects still deserves investigation. Flood experience could increase people's likelihood to take mitigation measures [26,41,42], there is also evidence that past experience does not contribute to a higher level of intention to take self-protective actions [28,43].…”
Section: Survey Development and Administrationmentioning
confidence: 99%
“…Logically, extreme weather must be perceived to be connected with climate change to have any relevance in informing climate change perceptions. While exposure to extreme weather may spontaneously update the perceived risk of subsequent adverse weather impacts (Frondel et al, 2017;Siegrist and Gutscher, 2006), more deliberate experience appraisal is required for extreme weather experiences to be interpreted in terms of climate change risk (Hamilton-Webb et al, 2017). In other words, extreme weather does not inherently signify climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Visschers and Siegrist [17] grouped research on risk into two categories: First, based on the psychometric paradigm, explains variations in perceptions of different risks whereas second examines the factors determining an individual's perception of a risk (i.e., perceived benefits, trust, knowledge, affective association, values, and fairness). Frondel et al [18] reported that the determinants of an individual's risk perception regarding climate change are associated with three kinds of natural hazards: heat waves, storms, and floods.…”
Section: Introductionmentioning
confidence: 99%